COMPARATIVE EFFICIENCY OF HEAT-PUMPS APPLICATION IN LOW TEMPERATURE HEAT SUPPLY SYSTEMS - M. N. Chepurnoy; N. V. Resident (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The  article  considers  comparative  operation-efficiency  of  the  low-temperature  heatsupply systems with heat pumping plants (HPP) and with hot-water boilers. The paper shows that for energy evaluation of the alternative heat-supply systems effectiveness one cannot employ the transformation ratio (heating coefficient) and the fuel heat-utilization factor in the HPP. Nonetheless the transformation ratio enters the formulae designating the efficiency of HPP operation. The authors obtain a generalized formula for ascertainment of transformation ratio and suggest evaluating the operation efficiency of the heat-supply systems by means of indicators specifying relative gain in the exergy-efficiency factor, fuel savings and saving expenditures connected with fuel and utilities. They attain formulae and build nomographic charts for those indicators ascertainment. The operation-efficiency comparative analysis of the low-temperature heat supply systems with HPP and with hot-water boilers shows that the HPP systems increase their effectiveness with transformation ratio, fuel price increase as well as with low electric-energy prices. The article specifies that with fuel low prices, the transformation-ratios limiting values with which the HPP operation-efficacy gains, grow. Energy-efficiency increase in the HPP does not always guaranty their economic effectiveness. These findings are true only for the heating systems. The hot water-supply systems will require the HPP condenser water additional heating to the assumed temperature from another thermal source, which reduces the effectiveness of the heat pump plants utilizing.